The problematic chemsex journey: a resource for prevention and harm reduction. Issue 1 (25th January 2019) - Platteau, Tom; Pebody, Roger; Dunbar, Nia; Lebacq, Tim; Collins, Ben
Abstract : Purpose: Chemsex is a phenomenon that has gained increasing attention in recent years. The purpose of this paper is to differentiate chemsex from other sexualized substance use, and clarify differences between recreational and problematic chemsex use. Despite plentiful publications, little has been published on underlying determinants that predispose individuals to chemsex, and their process toward problematic chemsex use. Design/methodology/approach: During the second European Chemsex Forum, people who engage in chemsex, community organizers, researchers, clinicians, therapists, social workers and (peer) counselors discussed potential pathways to problematic chemsex. In this manuscript, we translate findings from these discussions into a framework to understand the initiation and process toward problematic chemsex. Findings: Six stages (loneliness and emptiness, search for connection, sexual connection, chemsex connection, problematic chemsex and severe health impact) and a set of factors facilitating the transition from one stage to the next have been identified. Originality/value: It is hoped that this "Journey towards problematic chemsex use" will stimulate reflection and debate, with the ultimate goal of improving prevention and care for people engaging in chemsex.